2016
DOI: 10.3791/54479
|View full text |Cite
|
Sign up to set email alerts
|

Ferric Chloride-induced Murine Thrombosis Models

Abstract: Arterial thrombosis (blood clot) is a common complication of many systemic diseases associated with chronic inflammation, including atherosclerosis, diabetes, obesity, cancer and chronic autoimmune rheumatologic disorders. Thrombi are the cause of most heart attacks, strokes and extremity loss, making thrombosis an extremely important public health problem. Since these thrombi stem from inappropriate platelet activation and subsequent coagulation, targeting these systems therapeutically has important clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…The mouse model experiments were carried out in accordance to Cleveland Clinic Foundation IACUC-approved protocols, using ferric chloride (FeCl 3 )-induced vascular injury and thrombosis model in mouse [22]. For this, 8–12 week old male C57BL6 mice were anesthetized with a mixture of ketamine (100 mg/kg) and xylazine (10 mg/kg) via intraperitoneal injection, and anesthesia was confirmed by toe clipping.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse model experiments were carried out in accordance to Cleveland Clinic Foundation IACUC-approved protocols, using ferric chloride (FeCl 3 )-induced vascular injury and thrombosis model in mouse [22]. For this, 8–12 week old male C57BL6 mice were anesthetized with a mixture of ketamine (100 mg/kg) and xylazine (10 mg/kg) via intraperitoneal injection, and anesthesia was confirmed by toe clipping.…”
Section: Methodsmentioning
confidence: 99%
“…The end points of the experiment were: 1) when blood flow had ceased for >30 s due to vessel occlusion, or 2) if occlusion was not observed in 30 min after SK (free or vesicle-encapsulated) administration. In our experience with this model, at ~5 min after FeCl 3 -induced endothelial damage the thrombus occludes about 30–50% of the blood vessel and upon further growth of the occlusive thrombus, numerous larger cells (leukocytes) start to roll on the vessel wall at the proximal site of the thrombus and the blood flow usually stops within 2–3 min of the appearance of these large cells [22]. The thrombolytic effect was quantitatively expressed as ‘time to delay’ for vessel occlusion (blood flow cessation) if vessel was fully occluded before 30 min post-injury or the 30 min data point if vessel occlusion did not occur by 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Ferric chloride-induced carotid artery thrombosis was performed as previously described. 19,20 If blood flow continued for more than 30 minutes, the experiment was terminated, and 30 minutes was assigned for statistical analysis. In addition, a carotid artery thrombosis model induced by transplanting a segment of the epigastric artery into the carotid lumen was performed as previously described.…”
Section: In Vivo Thrombosismentioning
confidence: 99%
“…11 Although a recent study has shown the ability to perform MCA occlusion in a semiawake setting, the animal preparation is acute and does not allow longitudinal monitoring of stroke progression. 15 Other currently used models of ischemic stroke are through ferric chlorideinduced vascular thrombosis, 16 endothelin-1-induced vasoconstriction, 17 or thrombin injection. 18 However, these models also suffer from the drawbacks of using anesthetics, being acute preparations, and requiring invasive surgery without recovery to induce stroke.…”
Section: Introductionmentioning
confidence: 99%